(untitled) (International relations and international law Journal, 2020)
The article aims to examine the role of innovative technologies used in the COVID-19 pandemic in higher education and health. The study has found that digital strategies using innovative technologies help students adapt to the pandemic’s effects. This study highlights various innovative technologies that help health and education systems adapt to the implications of the COVID-19. The article discusses the technological changes in the world economy during the pandemic and its impact on modern society. In addition to the innovative technologies, this article examines the changes that have taken place in Kazakhstan’s education system during the pandemic. The literature review covers topics related to COVID-19 and digital education found in SCOPUS, Springer, Science Direct, and Google Scholar, using appropriate keywords. Relevant materials of sites and blogs are also taken into account. The list of essential technologies widely used during the pandemic in Kazakhstan has been identified. We used qualitative (59 respondents) and quantitative (98 respondents) research methods. The study results show that at the end of the 2019-2020 semester, students were informed on blended learning and its meaning. The scientific novelty describes the experience of Kazakhstani universities during the quarantine. We believe that blended learning should be widely used in the future. Innovations in the educational process cover two areas – the first concerns the software used to create a virtual university that facilitates communication between students and faculty. The second direction is related to the content of studying, without which innovations would fail.